Nonlinear associations of nighttime sleep and protective napping with depressive symptoms: a cross-sectional analysis from the China Family Panel Studies - Song, Yanliqing; Liu, Yue; Liu, Li (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to explore the relationship between nap duration, nighttime sleep, and depression among Chinese residents and determine recommended sleep durations to provide scientific evidence for the prevention and control of depression.MethodsBased on the 2020 China Family Panel Studies, demographic data, health, and lifestyle information was obtained from the study subjects. A total of 6,795 valid samples were included. Logistic regression, restricted cubic splines, and stratified linear regression analyses were used to examine the associations between sleep behaviors and depression, including subgroup analyses by health status and age categories.ResultsA U-shaped dose–response relationship was observed between nighttime sleep and depressive symptoms (P-nonlinear < 0.001), with the lowest likelihood of depression occurring around 8.5 hours of sleep. A nap duration of 30–90 minutes was associated with a lower likelihood of depression, with no evidence of a nonlinear relationship (P-nonlinear = 0.889). Subgroup analyses revealed that nighttime sleep of 7–9 hours was protective against depression among individuals with self-rated general health or chronic diseases. Age-stratified analyses showed that sleep behaviors had stronger protective effects in young adults (<30 years), whereas depression in middle-aged and older adults (≥30 years) was more influenced by chronic disease status and education level.ConclusionNighttime sleep of 7–9 hours and nap duration of 30–90 minutes are associated with reduced depressive symptoms; however, their effects vary across health and age subgroups. These findings highlight the importance of tailoring sleep recommendations to individual characteristics for effective mental health promotion.